2001
DOI: 10.1074/jbc.m101487200
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose Accumulation during Cellular Stress Protects Cells and Cellular Proteins from Damage by Oxygen Radicals

Abstract: The disaccharide trehalose, which accumulates dramatically during heat shock and stationary phase in many organisms, enhances thermotolerance and reduces aggregation of denatured proteins. Here we report a new role for trehalose in protecting cells against oxygen radicals. Exposure of Saccharomyces cerevisiae to a mild heat shock (38°C) or to a proteasome inhibitor (MG132) induced trehalose accumulation and markedly increased the viability of the cells upon exposure to a free radical-generating system (H 2 O 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
373
1
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 589 publications
(400 citation statements)
references
References 58 publications
13
373
1
13
Order By: Relevance
“…An increasingly wide range of functions are attributed to trehalose; for example, it is well known to act as an organic osmolyte in micro-organisms [17,[37][38][39] and it has also been implicated in the cold stress response of E. coli [15]. Heat shock and oxidative stress do not seem to activate tps genes in A. avenae, but this contrasts with the situation in micro-organisms, where trehalose is thought to play a role [13,14,16]. At present, other than a few studies in anhydrobiosis, there is sparse information on trehalose synthesis in nematodes [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasingly wide range of functions are attributed to trehalose; for example, it is well known to act as an organic osmolyte in micro-organisms [17,[37][38][39] and it has also been implicated in the cold stress response of E. coli [15]. Heat shock and oxidative stress do not seem to activate tps genes in A. avenae, but this contrasts with the situation in micro-organisms, where trehalose is thought to play a role [13,14,16]. At present, other than a few studies in anhydrobiosis, there is sparse information on trehalose synthesis in nematodes [40].…”
Section: Discussionmentioning
confidence: 99%
“…cerevisiae), the majority are not; accordingly, in the latter species, the role of trehalose is probably not related to desiccation tolerance. Rather, trehalose might be a general stress molecule, at least in micro-organisms, being linked to multiple stress responses, including those to heat [13,14], cold [15], reactive oxygen species [16] and elevated osmolarity [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, however, have demonstrated the ability of this disaccharide to protect cells against other types of aggressions, namely oxidative stress and heat stress. The role of trehalose as a scavenger of oxygen radicals has been shown in S. cerevisiae (Benaroudj et al, 2001). On the other hand, the accumulation of trehalose in response to elevated temperature has been reported in several mesophilic organisms, such as yeast, E. coli and Salmonella enterica (Strom & Kaasen, 1993;De Virgilio et al, 1994;Cánovas et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a number of studies have shown that trehalose can be used as an excellent alternative cryoprotectant in the cryopreservation of red blood and germ cells [13][14][15]. Another advantage of trehalose, as previously demonstrated, is its ability to inhibit the apoptosis level [16,17]. Because of the aforementioned advantages, trehalose has become a research hot spot in the cryopreservation field in recent years.…”
Section: Introductionmentioning
confidence: 98%